Immune response to vaccines is maintained in patients treated with dimethyl fumarate. Issue 1 (January 2018) - von Hehn, Christian; Howard, Jonathan; Liu, Shifang; Meka, Ven; Pultz, Joe; Mehta, Devangi; Prada, Claudia; Ray, Soma; Edwards, Michael R.; Sheikh, Sarah I.
Abstract : Objectives: To investigate the immune response to vaccinations in patients with relapsing forms of MS treated with delayed-release dimethyl fumarate (DMF) vs nonpegylated interferon (IFN). Methods: In this open-label, multicenter study, patients received 3 vaccinations: (1) tetanus-diphtheria toxoid (Td) to test T-cell–dependent recall response, (2) pneumococcal vaccine polyvalent to test T-cell–independent humoral response, and (3) meningococcal (groups A, C, W-135, and Y) oligosaccharide CRM197 conjugate to test T-cell–dependent neoantigen response. Eligible patients were aged 18–55 years, diagnosed with relapsing-remitting MS (RRMS), and either treated for ≥6 months with an approved dose of DMF or for ≥3 months with an approved dose of nonpegylated IFN. Primary end point was the proportion of patients with ≥2-fold rise in antitetanus serum IgG levels from prevaccination to 4 weeks after vaccination. Results: Seventy-one patients (DMF treated, 38; IFN treated, 33) were enrolled. The mean age was 45.3 years (range 27–55); 86% were women. Responder rates (≥2-fold rise) to Td vaccination were comparable between DMF- and IFN-treated groups (68% vs 73%). Responder rates (≥2-fold rise) were also similar between DMF- and IFN-treated groups for diphtheria antitoxoid (58% vs 61%), pneumococcal serotype 3 (66% vs 79%), pneumococcal serotype 8 (95% vs 88%), and meningococcal serogroup C (53% vs 53%), all p > 0.05. In a post hoc analysis, no meaningful differences were observed between groups in the proportion of responders when stratified by age category or lymphocyte count. Conclusions: DMF-treated patients mount an immune response to recall, neoantigens, and T-cell–independent antigens, which was comparable with that of IFN-treated patients and provided adequate seroprotection. ClinicalTrials.gov identifier: NCT02097849. Classification of evidence: This study provides Class II evidence that patients with RRMS treated with DMF respond to vaccinations comparably with IFN-treated patients.